FACTORS AFFECTING WASTE MANAGEMENT IN NORTH BUNTULIA VILLAGE, POHUWATO DISTRICT - Podungge, Abdul Wahab; Nuna, Muten; Junus, Dikson; arsjad, fachri; mokoginta, sumarti (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2024)
F The fact remains that waste management is still not given proper attention and is inadequately handled by various parties, despite being a shared responsibility. Improper waste management can lead to numerous environmental issues such as flooding, global warming, and the outbreak of various diseases. This article aims to identify and describe the factors influencing waste management in North Buntulia Village, Pohuwato District. The research method employed is qualitative, utilizing an interactive model analysis for data analysis. This model consists of three components: 1) Data reduction, 2) Data presentation, and 3) Data verification and conclusion drawing. The findings indicate that the factors influencing waste management include: 1) the size of the organization, 2) management style, 3) the complexity of the business environment, 4) the production process, and 5) the characteristics of the problems faced and the objectives of planning. This study recommends that the Regional Government of Pohuwato Regency.